Thermal conductive and flexible silastic composite based on a hierarchical framework of aligned carbon fibers-carbon nanotubes. (May 2018) - Ji, Tengxiao; Feng, Yiyu; Qin, Mengmeng; Li, Shuangwen; Zhang, Fei; Lv, Feng; Feng, Wei
Abstract: One-dimensional carbon structures are ideal fillers for improving the thermal conductivity (κ) of flexible carbon/polymer composites. However, the aligned pathways usually result in anisotropic heat conduction. Here, a three-dimensional (3D) hierarchical framework is fabricated by electrostatic flocking, using aligned carbon fibers and vertically aligned carbon nanotubes (CF-VACNTs). Theoretical simulations show that the VACNTs anchoring on the CFs improves the heat conduction of the composite in both the axial and the radial directions of the CFs, by absorbing and transferring heat from silastic (SI) matrix to CFs. The thermal conductivity in the through-thickness (κ⊥ ) and in-plane (κ∥ ) directions of aligned carbon fiber-carbon nanotube/silastic (ACF-VACNT/SI) composite could be improved by optimizing the CF transfixion structure and the VACNT network, through the length and rank of VACNTs and the alignment of CF-VACNTs. ACF-VACNT/SI with 60 μm in length and crisscross quadruple VACNT rows exhibits both a high κ⊥ (7.51 W mK −1 ) and a high κ∥ (3.72 W mK −1 ), suggesting good heat transfer in both two directions even under compression and bending. A thermochromic display device based on ACF-VACNT/SI confirms that the composite is suitable for application as thermal interface materials in wearable intelligent electronic devices. Graphical abstract: Image 1